Quantum Ring in a Magnetic Field: High Harmonic Generation and NOT Logic Gate. Issue 7 (14th June 2020) - Cricchio, Dario; Fiordilino, Emilio
Abstract: The effect of a static magnetic field on the high harmonic generation (HHG) from a quantum ring driven by one laser polarized along the x ‐axis is studied. The spin polarization S ( t ) and the temporal emission of the harmonics are studied by varying the intensity of the magnetic field and it is shown how these results have a significant technological impact in computer technology; in fact a boolean algebra can be implemented by assigning 0 and 1 values to low and high pulse intensities of the emitted harmonics and logic gates like the NOT can be created. Abstract : A laser pulse of frequency ω L stimulates a spin constrained on a nanoring to emit a wide spectrum of harmonics of ω L . Control of the time emission of the harmonics, achieved by piercing the ring with a static magnetic field B 0, permits fabrication of the optical logic gates operating in a time scale of 10 −15 s.